1996
DOI: 10.3181/00379727-213-44048
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Metabolism in Experimental Nephrosis

Abstract: In experimental nephrosis, a decrease in plasma albumin resulting from proteinuria causes a decreased in the plasma oncotic pressure. The existence of an osmoreceptor, which responds to the low oncotic pressure and produces a factor(s) that signals the liver to increase the secretion of plasma proteins, is postulated. The hyperlipidemia characteristic of the nephrotic syndrome results primarily from increased hepatic secretion of apolipoproteins and lipoproteins representing the entire density spectrum from VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…This was directly examined, and the results are shown in Fig. 2 In general, these data are consistent with the elevations of plasma cholesterol (total and HDL) and apo A-I observed in the classical rat model (8,9). The results also demonstrated equivalent effects of expressing either of the two h-apo A-I DNA constructs on the plasma levels of cholesterol (total or HDL) and apo A-I (human or mouse) in the nephrotic mice.…”
Section: Effects Of Nts On the Plasma Levels Of Lipids And H-apo A-i supporting
confidence: 66%
See 1 more Smart Citation
“…This was directly examined, and the results are shown in Fig. 2 In general, these data are consistent with the elevations of plasma cholesterol (total and HDL) and apo A-I observed in the classical rat model (8,9). The results also demonstrated equivalent effects of expressing either of the two h-apo A-I DNA constructs on the plasma levels of cholesterol (total or HDL) and apo A-I (human or mouse) in the nephrotic mice.…”
Section: Effects Of Nts On the Plasma Levels Of Lipids And H-apo A-i supporting
confidence: 66%
“…As noted in the Introduction and reviewed elsewhere (8,9), the experimental nephrotic syndrome is one of the most potent known inducers of hepatic apo A-I mRNA and protein, and a large component of this induction is transcriptional (10,11). Although the cis-acting factors for the liver-specific basal expression of the h-apo A-I gene had been shown in transgenic mice (12) to reside on the 256-bp fragment 5Ј to the transcriptional start site, there are currently no data concerning the metabolic regulation in liver of induced h-apo A-I gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the lipoprotein abnormalities in renal disease result from increased hepatic secretion of apo B-containing lipoproteins [5][6][7][8][9][10]. This appears to be a consistent finding in animal models of the nephrotic syndrome [2]. However, humans show variable metabolic patterns [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 74%
“…Dyslipidemia secondary to the nephrotic syndrome may consist of elevated levels of LDL alone or concomitantly elevated levels of LDL precursors, i.e., VLDL and IDL [1][2][3][4]. These lipoproteins are atherogenic and also may worsen renal function.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Furthermore, recent studies showed that triglyceride-rich proteins also have an important role. [17] Although total cholesterol, triglyceride, and LDL cholesterol levels of patients were significantly higher than those of controls, there was no correlation between CFR and lipid profiles of study subjects other than total cholesterol (r = −0.31, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%